A STUDY ON THE STUDENTS’ FACTOR DIFFICULTY IN WRITING NARRATIVE TEXT AT VIII GRADE OF MTs SABILAL MUHTADIN TEMBILAHAN - Nurul Asiah; Edi Ardian; Samsul Amri (Program Studi Pendidikan Bahasa Inggris, 2020)
Writing is one of the language skills, which is taught to secondary school students. In reality, it is still found that students have difficulties in writing. It is needed to investigate why it happened. Thus, the purpose of this research is to determine the students' factor difficulties in writing a narrative text. Moreover, it was designed as descriptive research which took sixty students of the eighth grade of MTs Sabilal Muhtadin Tembilahan as the samples. In collecting the data, the researchers used questionnaires and interviews. Then the data were analyzed by using descriptive statistical analysis and qualitative analysis. The research findings show that there are two main factors; students' factors and teachers' factors. After analyzing the data, the results revealed that the students' factor gained a percentage of 62.43% which was placed at a strong level. Also, the teachers' factor obtained a percentage of 72.95% which was classified as a strong level. The highest students’ factor indicator was the statement “English is very different from Bahasa Indonesia.